ANALYZING POPULATION DYNAMICS THROUGH DIFFERENTIAL EQUATIONS AND LAPLACE TRANSFORM METHODS (International Journal of Food and Nutritional Sciences, 2022)
Laplace transformation is an important chapter of Mathematical Analysis. It has wide application in different fields of techniques and engineering beside , basic sciences and mathematics. In this paper we will become acquainted with the basic concepts of operational mathematics, some properties of Laplace Transform and its application in demography. The purpose of this paper is to utilize the Laplace transformation to extract the logistic equation and to use the logistic equation in population growth.